Unlocking the Linguistics Wonders: From Bilingual to Code-mixing and Code-switching Utterances in Perspective Show on Metro TV - Dewirahmadanirwati Dewirahmadanirwati; Syahrul Ramadhan; Mukhaiyar Mukhaiyar (AL-ISHLAH: Jurnal Pendidikan, 2024)
In a world where bilingualism is prevalent, people often naturally use code-mixing and code-switching as expressive tools in their language activities. This research aims to analyze the types of code-mixing and code-switching, the reasons for their use, and the matrix language in the interview between Maudy Ayunda and Robert on Perspektif Metro TV. The study employs a descriptive qualitative method, with data obtained from the conversation between Maudy Ayunda and Robert. Using a qualitative approach and non-invasive observation techniques, the data were analyzed based on Hoffman's theory of code-mixing and code-switching. The results indicate that the speakers employed three types of code-mixing (intra-sentential, intra-lexical, and changes in pronunciation) and two types of code-switching (inter-sentential and establishing continuity with the previous speaker). The motivations for using these codes included discussing specific topics, quoting someone, emphasizing points, repeating for clarification, and explaining content to the interlocutor. Code-mixing was used more frequently than code-switching. In conclusion, Indonesian served as the matrix language and English as the embedded language in the instances of code-mixing and code-switching observed. The findings have significant implications for the education field, particularly in multilingual and bilingual settings. Recognizing and integrating code-mixing and code-switching as legitimate and beneficial linguistic practices can enhance language learning by creating an inclusive environment where students feel comfortable using multiple languages. Educators can leverage these practices to improve engagement, comprehension, and expression in complex subjects, fostering a deeper understanding and better communication skills among students. Future research should investigate these phenomena across diverse contexts and larger samples to further validate and extend these findings, thereby enriching bilingual education strategies.